Análise de viabilidade econômica da implantação do sistema integração lavoura-pecuária (iLP) no bioma cerrado - Possamai, Roberta Cristina (2017)
Under what technical and market conditions does an integrated croplivestock system (iLP) become economically viable in the Brazilian Savanna? Despite the productive and environmental advantages of the iLP systems and the conditions that make them technically feasible, the evaluation of their economic viability is fundamental for the implementation, consolidation and expansion of this modality of productive arrangement. The objective of this study is to evaluate under what technical and market conditions an iLP system becomes economically viable or ceases to be. In order to carry out such analysis, the analysis started with a representative (hypothetical) farm located in the Brazilian Savanna biome. The assessment of economic viability was based on the analysis of the Discounted Cash Flow of this farm and considered the 2016 economic and financial indicators as the base scenario. Based on that scenario, the study also evaluated how the economic viability of an iLP project changes from shocks on key variables. Among the results, it is noteworthy that, although the iLP system has proved to be economically profitable in most of the simulated scenarios, cyclical changes decisively affect the economic viability of the project.